SMART LOCKER BOX FOR STORING GOODS USING ESP 8266 AND SMART PHONE - suwondo, Adi; Ngatoilah, Mohammad (CATHA SAINTIFICA, 2024)
Storage of goods in public areas, such as in the Al Furqon Mosque, is often a problem due to the lack of adequate security systems due to the absence of guards. This raises the risk of losing goods, so an effective and efficient solution is needed. This study aims to design and implement an ESP 8266-based smart locker box that can be controlled via a smartphone to improve security and comfort in storing goods. The research method used is the waterfall system development model, which includes the stages of needs analysis, system design, code, testing, and maintenance. This system is designed using the ESP 8266 module as the main controller connected to a smartphone application via a Wi-Fi connection. The main features include automatic locking and opening of the locker and notification of locker status via the application. The results of the study show that the smart locker box functions well, with a fast and accurate control response via a smartphone. This system has succeeded in improving the security of goods in storage areas, especially in public places such as mosques, by reducing the risk of losing goods. The impact of this research is the creation of an innovative technological solution to overcome security problems in storage areas without guards, as well as increasing the sense of security and comfort for users